Additive-Free, Low-Temperature Crystallization of Stable α-FAPbI3 Perovskite - Du, Tian; Macdonald, Thomas J.; Yang, Ruo Xi; Li, Meng; Jiang, Zhongyao; Mohan, Lokeshwari; Xu, Weidong; Su, Zhenhuang; Gao, Xingyu; Whiteley, Richard; Lin, Chieh-Ting; Min, Ganghong; et al. (Advanced Materials, 2022)
Formamidinium lead triiodide (FAPbI3) is attractive for photovoltaic devices due to its optimal bandgap at around 1.45 eV and improved thermal stability compared with methylammonium-based perovskites. Crystallization of phase-pure α-FAPbI3 conventionally requires high-temperature thermal annealing at 150 °C whilst the obtained α-FAPbI3 is metastable at room temperature. Here, aerosol-assisted crystallization (AAC) is reported, which converts yellow δ-FAPbI3 into black α-FAPbI3 at only 100 °C using precursor solutions containing only lead iodide and formamidinium iodide with no chemical additives. The obtained α-FAPbI3 exhibits remarkably enhanced stability compared to the 150 °C annealed counterparts, in combination with improvements in film crystallinity and photoluminescence yield. Using X-ray diffraction, X-ray scattering, and density functional theory simulation, it is identified that relaxation of residual tensile strains, achieved through the lower annealing temperature and post-crystallization crystal growth during AAC, is the key factor that facilitates the formation of phase-stable α-FAPbI3. This overcomes the strain-induced lattice expansion that is known to cause the metastability of α-FAPbI3. Accordingly, pure FAPbI3 p–i–n solar cells are reported, facilitated by the low-temperature (≤100 °C) AAC processing, which demonstrates increases of both power conversion efficiency and operational stability compared to devices fabricated using 150 °C annealed films.
CRIS-Team Scopus Importer:2022-02-04